The ‘invisible’ needs of women with disabilities in transportation systems - Iudici, Antonio (Crime prevention and community safety, 2017)
Women with disabilities are among those who suffer most from sexual assault in transit environments. This paper offers a review of international literature concerning women’s victimisation and safety in transit environments with focus on (a) the concept of vulnerability, (b) data on victimisation in transport systems, (c) the perspective of criminals who target women with disabilities and (d) prevention policies and intervention strategies.